Public database mapping UK seafood supplies and nutrients(UK Data Service). - Anneli Löfstedt; Bernhard Scheliga; Magaly Aceves-Martins; Baukje de Roos (Data in Brief)
Here we present a high-resolution perspective on United Kingdom (UK) seafood supplies and nutrient flows between 2009 and 2020 with data collected from publicly available datasets. The database combines secondary data on production (capture and aquaculture), trade (import and export), purchases, and consumption, for up to 73 seafood species. The nutritional composition (protein, omega-3 fatty acids, vitamin D, vitamin A, vitamin B12, calcium, iodine, iron, selenium, and zinc) for each species are also included. As the secondary data was obtained from different data sources, they were harmonised to efficiently link the data. Seafood species were categorised as lean, oily, and shellfish, to allow comparisons with UK dietary guidelines, and were assigned a species type according to the Food and Agricultural Organisation 'International Standard Statistical Classification for Aquatic Animals and Plants' classification. By the virtue of the integrated nature of our seafood database, it provides a unique opportunity for users to interrogate the entire UK seafood supply chain, at a species level, over a decade worth of data, allowing users to understand what seafood is being produced and ultimately consumed. The application of this database is described in an original research article entitled “Seafood supply mapping reveals production and consumption mismatches and large dietary nutrient losses through exports in the United Kingdom”.